ANALYSIS OF THE STARTING LEVEL OF COMPUTER DEPENDENCE OF STUDENTS - Y. Kulikova; T. Penkova (Вестник Северо-Кавказского федерального университета)
Modernization of the modern education system, the availability of computer technology is one of the most striking events of our time. Almost every educational institution or organization is equipped with a computer and computer networks. The active introduction of computer technology in everyday life, ofcourse, leaves a certain imprint on the formation and development of personal qualities. This article discusses the problems of Internet addiction of students suffering from this disease. The results of diagnosing students of the 10th and 11th university profile classes of the Pedagogical Institute of the Federal State Budget Educational Establishment of Higher Education "Tambov State University named after G.R. Derzhavin «, in order to identify the level of computer addiction.